Pengujian Efek Fisher Internasional: Studi Kasus Indonesia Dan China - Ernawati Nurul Hidayah; Z. Zainuri; Anifatul Hanim (UPT Penerbitan Universitas Jember, 2018)
The fluctuation of rupiah exchange rate caused by the application of open economy system especially with China in ACFTA international organization, which has good economy and influences in global can draw China as the worthy country in takin the policy through monetary variables. The purpose of this research is to know the short term and long term influence of the differences in Indonesia-China interest, the differences of Indonesia-China inflation, and Yuan exchange rate to rupiah exchange rate based on international fisher effect theory. This research focuses on quantitative analysis by using Error Correction Model (ECM) method. Short term ECM estimation shows that the relation between differences of interest, differences of inflation with rupiah exchange rate is not suitable with international fisher effect theory because is has positive and insignificant relation, yuan exchange rate with rupiah exchange rate is suitable with theory because is has negative. Then, the result of short term ECM estimation shows that there is a gap so the determination of rupiah exchange rate is dominated by Yuan exchange rate. The relation between the difference of interest and the difference of inflation is contrary with the theory and it is only Yuan exchange rate that has the relation with rupiah exchange rate and it is suitable with international fisher effect theory. Keywords: international fisher effect theory, rupiah exchange rate, interest, inflation, error correction model (ECM) analysis